Rotation Stiffness Investigation of Spatial Joints with End-Plate Connection - Shizhe Chen; Jianrong Pan; Zhan Wang; Chao Zhou (Advances in Civil Engineering)
Spatial joints with end-plate connections show significant spatial coupling effects under spatial loading. Mechanical behaviour and failure modes of these spatial joints differ from those of planar joints. This study involved experiments and finite element analyses with respect to planar joints with end-plate connections under static load. The numerical results agreed well with the experimental data, and this verified the adequacy of the finite element analyses. Then, finite element models of the spatial interior joint, exterior joint, and corner joint were established to analyse the difference between the mechanical behaviour of spatial joints and planar joints. The component method was used to analyse components contributing to the initial stiffness of spatial joints. An initial rotation stiffness calculation model of spatial joints was proposed based on the deformation of joints. The findings indicated that results of the calculation models were in good agreement with those of the finite element analyses, and this proved that the calculation model proposed in this study could act as a reference method.